Divergent impacts of quantity versus price-based monetary policies on banking systemic risk: Evidence from China - Yichao Mo; Weihong Sun; Youqiang Ding; Li Wang (PLoS ONE, 2025)
This study investigates the effects of price-based (PMP) and quantity-based monetary policies (QMP) on systemic risks within China’s banking sector. We identify exogenous components of PMP and QMP by isolating explicit structural shocks in a structural vector autoregression model. Systemic risks are categorized into bottom-up risks, which assess how the distress or default of a single bank can contribute to systemic vulnerabilities, and top-down risks, which evaluate the likelihood of a bank experiencing distress during financial market turbulence. Utilizing a smooth local projection model, we analyze the impact of PMP and QMP on these two types of systemic risks. Our findings reveal that contractionary PMP shocks exacerbate bottom-up systemic risks while mitigating top-down risks. In contrast, contractionary QMP shocks initially elevate but subsequently diminish bottom-up risks, with minimal impact on top-down risks. Importantly, PMP affects state and non-state banks differently, decreasing top-down risks in state banks but increasing them in non-state banks. This differential impact indicates that the risk-taking behavior of non-state banks triggered by contractionary PMP can spill over, amplifying the damage of financial distress for both state and non-state banks.